Apoptotic Vesicles Derived from Mesenchymal Stem Cells Ameliorate Hypersensitivity Responses via Inducing CD8+ T Cells Apoptosis with Calcium Overload and Mitochondrial Dysfunction - Anqi Liu; Peng Peng; Changze Wei; Fanhui Meng; Xiaoyao Huang; Peisheng Liu; Siyuan Fan; Xinyue Cai; Meiling Wu; Zilin Xuan; Qing Liu; Xinyu Qiu; et al. (Advanced Science)
Abstract Apoptosis is crucial for maintaining internal homeostasis. Apoptotic vesicles (ApoVs) derived from mesenchymal stem/ stromal cells (MSCs‐ApoVs) as natural lipid nanoparticles are attractive candidates for the next generation of immunotherapies. However, the therapeutic potential of MSCs‐ApoVs in managing hypersensitivity reactions mediated by CD8+ T cells remains elusive. This research utilized contact hypersensitivity and oral lichenoid reaction models, both of which represent type IV hypersensitivity reactions. ApoVs are shown that derived from stem cells from human exfoliated deciduous teeth (SHED‐ApoVs), a subtype of MSCs, directly fused with the plasma membrane of CD8+ T cells, subsequently increasing membrane permeability through L‐type voltage‐gated Ca2+ channels. This initiates a cascade of events including calcium overload, mitochondrial dysfunction, and the initiation of apoptosis in these cells. As known, this is the first study to characterize SHED‐ApoVs as immune microenvironment modulators, demonstrating their therapeutic potential and mechanism in these reactions. Moreover, analysis of blood samples from patients with oral lichenoid reactions verified the antihypersensitivity property of SHED‐ApoVs. This study sheds light on the therapeutic prospects of MSCs‐ApoVs and their underlying mechanisms in diseases mediated by CD8+ T cells, contributing novel perspectives for the clinical application of ApoVs and nanovesicle‐based cell‐free therapies.